2022
DOI: 10.3389/fpls.2022.1043171
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol and plant growth promotion by combined Bacillus spp. inoculation affecting pathogen and AMF communities in the wheat rhizosphere at low salt stress conditions

Abstract: Applying plant growth-promoting rhizobacteria (PGPR) improves the efficiency of soil-borne disease control and is considered a sustainable practice. However, the effect of PGPR on the fungal community, especially pathogenic fungi and arbuscular mycorrhizal fungi (AMF), remains unclear. In this study, we examined the effects of a compound microbial agent (consisting of Bacillus subtilis HG-15 and Bacillus velezensis JC-K3) on the incidence and yield of wheat under low salt stress, as well as compared the divers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…The rational use of AMF with other microorganisms maximizes plant tolerance to diseases by competing with harmful pathogens (Devi et al 2022). Studies have also revealed that the combined application of AMF and other beneficial plant microorganisms like plant growth-promoting rhizobacteria (PGPRs) impacts plant root exudation, thereby altering the rhizosphere niche (Ji et al 2022). Furthermore, deciphering the far-reaching changes in plant metabolome, microbiome, and molecular reprogramming under the influence of AMF in diseased and non-diseased conditions will provide better outcomes in AMF-mediated plant disease management.…”
Section: Introductionmentioning
confidence: 99%
“…The rational use of AMF with other microorganisms maximizes plant tolerance to diseases by competing with harmful pathogens (Devi et al 2022). Studies have also revealed that the combined application of AMF and other beneficial plant microorganisms like plant growth-promoting rhizobacteria (PGPRs) impacts plant root exudation, thereby altering the rhizosphere niche (Ji et al 2022). Furthermore, deciphering the far-reaching changes in plant metabolome, microbiome, and molecular reprogramming under the influence of AMF in diseased and non-diseased conditions will provide better outcomes in AMF-mediated plant disease management.…”
Section: Introductionmentioning
confidence: 99%
“…Photosynthetic electron transport in photosystem I, photosynthesis, dark reactions, and the reductive pentose-phosphate cycle were the main types of biological processes in leaves ( Figure 2D ). This indicated that the BIO treatment mobilized the primary and secondary metabolisms and finally regulated the expression of related genes through signal transduction and ion transport, which clearly induced the salt stress defense responses and had the greatest effects on ion absorption and antioxidant activity of wheat root cells and on the photosynthesis of leaf cells ( Abdelgawad et al., 2022 ; Ji et al., 2022a ).…”
Section: Discussionmentioning
confidence: 99%
“…Bacillus velezensis JC-K3 and Bacillus subtilis HG-15 are two strains of rhizosphere-beneficial bacteria with both growth-promoting and disease-preventing functions ( Ji et al., 2021 ; Ji et al., 2022b ). The two strains have no antagonistic effects and can stably colonize wheat roots in saline-alkali land.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Halotolerant PGPRs with 1-aminocyclopropane-1-carboxylic acid (ACC) deaminase activity can reduce plant ethylene accumulation, prevent oxidative stress, promote plant growth, and regulate the rhizosphere microbial community structure. Consequently, halotolerant PGPRs have become a valuable microbial resource for promoting crop growth in saline-alkali soils ( Ji et al, 2022a ; Li et al, 2023 ). Among the beneficial microorganisms in saline soils, ascomycetous fungi (AMF) can form a symbiotic relationship with most crops, improving soil nutrient acquisition, promoting plant growth and water absorption, and initiating defense responses in host plants ( Bennett and Groten, 2022 ).…”
Section: Introductionmentioning
confidence: 99%